Strategi SMPN 1 Cisarua Menjaga Lingkungan Sekolah Menjadi Sekolah Adiwiyata - Thaliana Primawardani, Astried; Sigarlaki, Nadya Aurelya; Logayah, Dina Siti; Jupri, Jupri (Education and Development Research, 2024)
Abstract: Adiwiyata school is a school that is running a program and implementing an education system that leads to awareness and culture of the school community towards the cleanliness of the school environment. This Adiwiyata award is an award given directly by the government to schools that have successfully implemented environmental education in schools. This award is also given as a form of appreciation to schools that have implemented the Adiwiyata program in accordance with the procedures provided by the government. The purpose of writing this article is to find out the strategies and methods used by SMPN 1 Cisarua in running the Adiwiyata school program. This research method uses a qualitative method with a description approach. The results of this study are that SMPN 1 Cisarua has a special way and strategy in running the Adiwiyata school program, so that it can win the award in 2022. Abstrak: Sekolah adiwiyata merupakan sekolah yang sedang menjalankan program dan melaksanakan sistem pendidikan yang mengarah kepada kesadaran dan budaya warga sekolah terhadap kebersihan lingkungan sekolah. Penghargaan adiwiyata ini, merupakan penghargaan yang diberikan langsung oleh pemerintah kepada sekolah yang telah berhasil menerapkan pendidikan lingkungan hidup di sekolah, penghargaan ini juga diberikan sebagai bentuk apresiasi kepada sekolah yang sudah menjalankan program adiwiyata sesuai dengan prosedur yang diberikan pemerintah. Tujuan penulisan artikel ini, untuk mengetahui strategi, dan cara yang dilakukan oleh SMPN 1 Cisarua dalam menjalankan program sekolah adiwiyata. Metode penelitian ini menggunakan metode kualitatif dengan pendekatan deskripsi. Hasil dari penelitian ini yaitu, SMPN 1 Cisarua memiliki cara dan strategi khusus dalam menjalankan program sekolah adiwiyata, sehingga dapat memenangkan penghargaan tersebut pada tahun 2022.